Framing challenges and polarized issues in invasion science: toward an interdisciplinary agenda - Guareschi, Simone; Mathers, Kate L; South, Josie; Navarro, Laetitia M; Renals, Trevor; Hiley, Alice; Antonsich, Marco; Bolpagni, Rossano; Bortolus, Alejandro; Genovesi, Piero; Jere, Arthertone; Madzivanzira, Takudzwa C; et al. (Bioscience, 2024)
In a hyperconnected world, framing and managing biological invasions poses complex and contentious challenges, affecting socioeconomic and environmental sectors. This complexity distinguishes the field and fuels polarized debates. In the present article, we synthesize four contentious issues in invasion science that are rarely addressed together: vocabulary usage, the potential benefits of nonnative species, perceptions shifting because of global change, and rewilding practices and biological invasions. Researchers have predominantly focused on single issues; few have addressed multiple components of the debate within or across disciplinary boundaries. Ignoring the interconnected nature of these issues risks overlooking crucial cross-links. We advocate for interdisciplinary approaches that better integrate social and natural sciences. Although they are challenging, interdisciplinary collaborations offer hope to overcome polarization issues in invasion science. These may bridge disagreements, facilitate knowledge exchange, and reshape invasion science narratives. Finally, we present a contemporary agenda to advance future research, management, and constructive dialogue.
Keywords: human–wildlife interactions; invasion science; natural resource management; conservation biology; invasive species